A level set approach for damage identification of continuum structures based on dynamic responses. (6th January 2017) - Zhang, Weisheng; Du, Zongliang; Sun, Guo; Guo, Xu
Abstract: The present paper aims to propose a novel approach for damage identification of continuum structures based on their dynamic performances. The main idea is resorting to the level set model, which is used to describe the shape and topology of the damage regions implicitly. The original natural frequency-based inverse problem is thus transferred into a generalized shape optimization problem which can be tackled by solving an evolution type Hamilton–Jacobi equation. Compared to traditional approaches, the distinctive advantage of the proposed approach is that it can deal with damage regions of complex shapes in a convenient way. Numerical examples demonstrate the effectiveness of the proposed approach.